1987
DOI: 10.3354/meps040115
|View full text |Cite
|
Sign up to set email alerts
|

Cold seep benthic communities in the Japan subduction zones: spatial organization, trophic strategies and evidence for temporal evolution

Abstract: Submersible exploration of the Japan subduction zones has revealed benthic communities dominated by clams (Calyptogena spp.) around sed~ment porewater seeps at depths from 3850 to 6000 m. Photographic and video records were used to produce microcartographlc reconstructions of 3 contrasting cold seep sites. Spatial and abundance relations of megafauna lead us to propose several hypotheses regard~ng the ecological functioning of these cold seep communities. W e dlst~nguish between the likely direct use of reduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(38 citation statements)
references
References 12 publications
0
37
0
Order By: Relevance
“…The first cold seep was discovered in 1979 on the active margin of San Clemente in California (USA) (Sibuet and Olu 1998). Since then, other cold seeps have been found on the passive margin of Florida (USA) in the Gulf of Mexico, on the subduction zones of Oregon (USA) and Japan, and the Barbados accretionary prism (Juniper and Sibuet 1987;Olu et al 1996). In Europe, cold seeps have also been found on the Norwegian margin, in the Gulf of Cadiz and the Mediterranean Sea and references therein; Ritt et al 2010;Zeppilli et al 2011Zeppilli et al , 2012.…”
Section: Cold Seepsmentioning
confidence: 99%
“…The first cold seep was discovered in 1979 on the active margin of San Clemente in California (USA) (Sibuet and Olu 1998). Since then, other cold seeps have been found on the passive margin of Florida (USA) in the Gulf of Mexico, on the subduction zones of Oregon (USA) and Japan, and the Barbados accretionary prism (Juniper and Sibuet 1987;Olu et al 1996). In Europe, cold seeps have also been found on the Norwegian margin, in the Gulf of Cadiz and the Mediterranean Sea and references therein; Ritt et al 2010;Zeppilli et al 2011Zeppilli et al , 2012.…”
Section: Cold Seepsmentioning
confidence: 99%
“…In shallower (from 4981 to 5938 m) cold seep communities in the Japan Trench (dominated by Calyptogena phaseoliformis), numerous actinians, buccinid and rissoacean gastropods, tubedwelling polychaetes, capreilid amphipods, and swimrning holoihurians (Pem'agone sp.) are consistenily associated with Calyptogena aggregations (Juniper & Sibuet 1987, Ohta & Laubier 1987, Sibuet et al 1988), but they were not observed in these thyasirid aggregations. The tubes observed at this site were curved and sparsely distributed, while those tubes commonly observed within Calyptogena-dominated sites are straight and densely packed.…”
Section: Introductionmentioning
confidence: 94%
“…Sulfide for these thyasirid aggregations may be produced in this way, using methane as a n energy source. The distnbution of this comrnunity seems more restncted than seep communities in other areas, such as Sagami Bay (Hashimoto et al 1989, the Nankai accretionary prism (Juniper & Sibuet 1987, Ohta & Laubier 1987, Sibuet et al 1988), Monterey Bay (Barry et al 1996), the Peruvian active margin (Olu et al 1996a) and the Barbados prism (Olu et al 199613). Detailed observations show that the newly discovered communities differ in other aspects as weil.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations